Employee Perceptions and Competences in Batam City Private Companies Facing Digital Finance Development - Indrayani Indrayani; Delila Putri Sadayi; Angelina Eleonora Rumengan; Reza Safitri (Universitas Dharma Wacana, 2022)
The transformation and development of digital finance have become an important issue in today's business world. Private companies in Batam City are also experiencing the impact of this transformation. This study aims to analyze employee perceptions and competencies in dealing with the transformation and development of digital finance in private companies in Batam City. This research focuses on understanding how employees perceive digital financial transformation and to what extent they have the necessary competencies to adapt to these changes. This study interviews and observes Batam City private company employees for qualitative data analysis. The systematic analysis was analyzed the data. This study found that most employees see digital finance transition positively. Digital finance may improve efficiency, engagement, and financial information accessibility. This research also finds different employee challenges in digital finance transformation. One is a need for digital technology and financial competence. Employees need help to adapt and maximize digital finance's potential. Thus, employee proficiency in digital financial transformation requires training and skills development. This study offers light on Batam City private company employees' views of digital finance's evolution. Positive impressions suggest digital finance can boost employee productivity and participation in firm financial tasks. However, training and skills development must overcome competency issues. Thus, organizations must focus on personnel development throughout digital financial transformation to ensure business success and continuity.